2015
DOI: 10.1016/j.proeng.2015.08.571
|View full text |Cite
|
Sign up to set email alerts
|

A Self-doping Surface Effect and its Influence on the Sensor Performance of Undoped SnO2 Based Gas Sensors

Abstract: The variation of the calcination temperature in the fabrication procedure of sol-gel SnO 2 thick film gas sensors leads to very different sensing characteristics [1]. In the present studies, the conduction mechanism and electrical characteristics of the surface of undoped SnO 2 based sensing materials -calcined at different temperatures -are investigated by performing DC electrical resistance and work function changes measurements. The results show for the first time the existence of an intrinsic surface band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…Afterwards, the product was divided into two samples, one calcined at 450 °C (SnO2-450) and the other at 1000 °C (SnO2-1000) for 8 h under air leading to surface areas of 32.7 and 3.6 m 2 g -1 , respectively. Spectroscopic investigations by DRIFTS [34,35] and UV/vis-DRS [36] and electronic studies of the conduction mechanisms [37,38] for two base materials are reported elsewhere. The spectroscopic investigations reveal strong difference in the surface chemistry and optical band gap, while the electronic studies exhibit the same conduction mechanism for both materials, namely a depletion layer-controlled conduction involving grains with an unaffected bulk region.…”
Section: Sno2 Synthesismentioning
confidence: 99%
“…Afterwards, the product was divided into two samples, one calcined at 450 °C (SnO2-450) and the other at 1000 °C (SnO2-1000) for 8 h under air leading to surface areas of 32.7 and 3.6 m 2 g -1 , respectively. Spectroscopic investigations by DRIFTS [34,35] and UV/vis-DRS [36] and electronic studies of the conduction mechanisms [37,38] for two base materials are reported elsewhere. The spectroscopic investigations reveal strong difference in the surface chemistry and optical band gap, while the electronic studies exhibit the same conduction mechanism for both materials, namely a depletion layer-controlled conduction involving grains with an unaffected bulk region.…”
Section: Sno2 Synthesismentioning
confidence: 99%
“… 19 Recently, tin oxide has received widespread attention in the field of pharmaceutical research as a result of its application in monitoring the drug release by fluorescent signal. 20 Tin oxide is an n-type semiconductor with chemical stability, high specific surface area and good biocompatibility, has optical properties in the visible spectral range and is extensively used in the fields of transparent conductors, 21 gas sensors, 22 biosensors, 23 catalysis, 24 energy storage 25 and medicinal applications. 26 , 27 However, so far, there have been no previous reports of the oral administration of mesoporous tin oxide-based formulations.…”
Section: Introductionmentioning
confidence: 99%
“…SnO2 is a semiconductor material with an energy band gap of about 3.6 eV and is sensitive to the presence of gas (Susilawati, et al, 2020). Based on these properties, SnO2 is widely applied to gas sensors (Rebholz, et al, 2015), optoelectronic equipment (Ikraman, et al, 2017), solar cells (Bittau, et al, 2017), capacitors , liquid crystal displays (Andrade, et al, 2019), diode (Gullu, et al, 2020), and transistor (Liu, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%